Ghayra i namus a zjawisko zbrodni „honorowych” w społecznościach muzułmańskich – zarys problemu - Sadowa, Katarzyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Although it is not a new problem, the phenomenon of ‘honour’ killings remains a legitimate threat. According to the relatively popular thesis presented by the media, this problem is closely linked to the Muslim religion. This article aims to answer the question of whether there is an actual (direct or indirect) connection between ‘honour’ killings and Islam. To that end, the author submits the Muslim concept of purity to analysis, focusing on ‘protective jealousy’ – ghayra and the particular nature of honour – namus
Keywords: ghayra; namus; zabójstwa honorowe; islam